Pengaruh Motivasi Dan Fasilitas Pembelajaran Terhadap Prestasi Belajar Siswa Kelas Tinggi Sd Negeri Gumpang 01 Kartasura Tahun Pelajaran 2015/2016 - UTAMI, DIKA ADI, Drs. Saring Marsudi, SH. M.Pd (2016)
The aims of this study is to find: (1) Determine the influence of motivation on student achievement of high grade primary school Gumpang 01 Kartasura the Academic Year 2015/2016. (2) Determine the influence of learning facilities on student achievement of high grade primary school Gumpang 01 Kartasura the Academic Year 2015/2016. (3) Determine the influence of motivation and learning facility to the achievement of high-grade primary school students Gumpang 01 Kartasura in academic year 2015/2016. This research includes quantitative research. The population in this study were 145 high-grade primary school students Gumpang 01 Kartasura. The sample in this study were 60 students of high grade. Data collection techniques in this study was a questionnaire and documentation. Data analysis technique used is multiple linear regression analysis, t test, F test, the coefficient of determination, SR and SE. Based on the results of multiple linear regression equation Y = 10,424 + 0,335x1 + 0,324x2 .The results of the analysis of data by the economic situation of significance 5 % obtained: ( 1 ) motivation impact on student learning achievements .It is based on the t be seen that tcalculation > ttabel , namely 2,410 > 2,002 and value significance < 0.05 namely 0,019 with contributions relatively of 47,9067 % and contributions effective of 22,085 % .( 2 ) learning facility impact on student learning achievements .It is based on the t be seen that tcalculation > ttabel , namely 2,590 > 2,002 and value significance < 0.05 namely 0,012 denngan contributions relatively of 52,0930 % and contributions effective 24,0149 % . ( 3 ) motivation and learning facilities impact on student learning achievements .It is based on the f be seen that fcalculation > ftabel namely 24,383 > 3.15 and value significance < 0.05 namely 0,000 .Based on the calculation on the coefficients determination known that the impact of motivation and learning facilities parental supervision and environment of the to student learning achievements contributed of 46.1 % and 53,9 % influenced by the other factors that aren t pursuing.